Catheter-induced 3:1 second degree atrioventricular nodal block during atrioventricular nodal reentrant tachycardia - Leandro Ioschpe Zimerman; Claudio Meirelles Medeiros; Gustavo Glotz de Lima (1999)
Catheter-Induced 3:1 Second Degree Atrioventricular Nodal Block During Atrioventricular Nodal Reentrant Tachycardia Case ReportSecond-degree atrioventricular (AV) nodal block with 2:1 AV conduction during atrioventricular nodal reentrant tachycardia (AVNRT) has been previously described.We report a patient who developed AVNRT during which 3:1 intra-infra-Hisian block due to catheter manipulation was observed.This was followed by gradual, incremental recovery of AV conduction.AVNRT accounts for approximately 50% of cases of supraventricular tachycardia.This mechanism of tachycardia uses a reentrant circuit in the region of the AV Node which usually contains distinct slow and fast pathways.Radiofrequency ablation of the slow pathway is an effective and safe treatment for AVNRT 1 .In this report, we present a patient with AVNRT of the common type who developed 3:1 intra-infra-Hisian block during AVNRT as a result of catheter manipulation.Before resumption of normal 1:1 conduction, we observed split His potentials in normal sinus rhythm, followed by atrioventricular (AV) nodal echo beats with intra-infra-Hisian block.